Ansvar utan klander? - Dag Victor (Nordisk Tidsskrift for Kriminalvidenskab)
Is penal liability for legal persons compatible with the humanistic ideology of the Enlightenment period? In penal law, the principle of guilt has been seen as an expression of this ideology. The notion of personal guilt cannot be applied to legal persons. It makes, however, perfect sense to censure acts and omissions in the business activities of a legal person. There is a tendency to use sanctions against legal persons according to the principle of strict liability. Such liability is liability without guilt but also without censure. It is argued that in penal law the requirement of censure is more central than guilt as a protection against state power. In that sense, it is in accordance with the heritage of the Enlightenment period to favour penal liability for legal persons in order to uphold the requirement of censure, even if this is a divergence from the principle of guilt.